Graded motor imagery as an adjunct to comprehensive physiotherapy in chronic rotator cuff-related pain: a single blind randomized controlled trial - Seda Sırlan; Nuray Alaca; Hacı Ahmet Yarar; Onur Başcı (BMC Musculoskeletal Disorders, 2025)
Abstract Background Chronic rotator cuff-related shoulder pain (C-RCRSP) may involve central sensitization and cortical changes. Graded motor imagery (GMI) targets these mechanisms, but its use in C-RCRSP is underexplored. Objective This study aims to evaluate the effects of GMI to comprehensive physiotherapy on pain, mechanical sensitivity, laterality judgment, motor imagery ability, central sensitization symptoms, two-point discrimination, pain-related fear and patient satisfaction in patients with C-RCRSP. Methods In this single-blind randomized controlled trial, 30 participants with C-RCRSP were randomized into two groups: comprehensive physiotherapy alone (CP) or combined with GMI (CP + GMI). Interventions were delivered twice weekly for six weeks. Outcomes included pain intensity, mechanical sensitivity, two-point discrimination, functionality, laterality judgment, motor imagery ability, central sensitization symptoms, pain-related fear and patient satisfaction. Results Both groups showed significant within-group improvements in pain intensity, range of motion, functionality, and pain-related fear (p < 0.05). The CP + GMI group demonstrated earlier reductions in pain intensity and improvements in mechanical sensitivity, laterality judgment, motor imagery skills (p < 0.05). No significant differences were found within or between groups in central sensitization symptoms and two-point discrimination (p > 0.05). A higher proportion of participants in CP + GMI rated their recovery as "much better" compared to CP (p = 0.05). Conclusion This study highlights that both groups showed significant improvements in pain, range of motion, functionality, and pain-related fear. However, adding GMI therapy led to faster pain relief, better mechanical sensitivity, improved motor imagery skills, and greater treatment satisfaction, warranting further research with larger samples and extended follow-ups to confirm its broader applicability. Trial registration The study was approved by the local ethics committee (Reference No. ATADEK- 2023/21–13) and registered as a US National Library of Medicine Clinical Trial (Registration No: NCT06092489, Date: 13.10.2023).